2023
DOI: 10.1371/journal.pone.0282046
|View full text |Cite
|
Sign up to set email alerts
|

The socio-demographic, clinical characteristics and outcomes of tuberculosis among HIV infected adults in Lithuania: A thirteen-year analysis

Abstract: Background Tuberculosis (TB) is a public health problem in Lithuania, among the 18 high-priority TB countries in the European region, and the most common AIDS-indicative disease with the highest proportion in the EU/EEA since 2015. The study aimed to identify socio-demographic, clinical characteristics and their relationship with TB outcomes in TB-HIV co-infected patients in Lithuania. Methods A retrospective chart review analysed the characteristics of TB-HIV co-infected adults registered in State Informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Although it is difficult to directly compare very heterogenous cohorts, a recent systematic review found pooled TBrecurrence rates of 4.5 (3.2-5.8) per 100 PYFU among PWH, with higher TB background incidence leading to higher TB recurrence rates [13,17]. In a recent study of PWH treated for TB in Lithuania, 34% developed a recurrent episode of TB, with a median time to recurrence of 4.5 years [14]. Conversely, a study including HIVnegative patients treated for MDR-TB in Russia reported very low recurrence rates after the first year of posttreatment follow-up [0.18/100 PYFU (0.05-0.3)] [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to directly compare very heterogenous cohorts, a recent systematic review found pooled TBrecurrence rates of 4.5 (3.2-5.8) per 100 PYFU among PWH, with higher TB background incidence leading to higher TB recurrence rates [13,17]. In a recent study of PWH treated for TB in Lithuania, 34% developed a recurrent episode of TB, with a median time to recurrence of 4.5 years [14]. Conversely, a study including HIVnegative patients treated for MDR-TB in Russia reported very low recurrence rates after the first year of posttreatment follow-up [0.18/100 PYFU (0.05-0.3)] [15].…”
Section: Discussionmentioning
confidence: 99%
“…Similar prevalence rates have been estimated in other European countries, such as The Netherlands and Finland [ 18 , 19 ]. A few studies of causes, socio-demographic factors, clinical presentation, and outcomes of infectious diseases have been conducted in Lithuania [ 15 , 20 ]. For example, Matulyte et al investigated data of patients with a diagnosis of bacterial meningitis treated between 2009 and 2016 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…TB continues to be a public health problem in Lithuania, as one of the 18 high-priority TB countries in the European region. Lithuania has one of the highest rates of TB in the European region (ranging from 40.7/10,000 in 2018 to 26.3/100,000 in 2022) [ 1 , 12 , 13 , 14 , 15 , 16 ] and out of the cumulative number of all 3431 PLHIV in Lithuania at the end of 2020 [ 17 ], 311 (9.1%) patients were registered with active TB [ 18 ]. TB is the most common AIDS-defining condition in Lithuania; its proportion has been the highest in the EU/EEA since 2015 and was still >50% of all AIDS-defining conditions in 2019 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%